IMPLEMENTASI NILAI-NILAI ISLAM PADA PRAKTIK SUMBER DAYA MANUSIA DI RUMAH ZAKAT SEMARANG - Alin, Atika Nur; Djastuti, Indi (Diponegoro Journal of Management, 2017)
Human resource management has a field management to specialized learn about relations and role of human hearts as well as the organization of the Company. Increased competition in the work environment is one of the most important reason for the spread of the role and importance of human resource management functions in the organization. Management of the majority of people know about the management of the western system. But with the economic development of Islam raises new phenomenon, especially on the side of the practitioner or human resources. Economic development of Islam practice in Indonesia is marked by the growth and development sector economic activities that utilize the principles of Islamic economics. As such, to be seen whether the organizations using the principles of Islamic economics has implemented management based on Islamic values that based Al-Quran and Hadith. This study was conducted to identify the implementation’; implementation of Islamic values in human resources practices in Rumah Zakat Semarang. These aspects are examined in this study, namely recruitment, selection and placement, training and development, performance appraisal, and compensation . This study uses a qualitative method where data collection is by interview, observation and documentation so that they can dig deep and detailed on the implementation of Islamic management in human resources management. Objects in this study are employees of Rumah Zakat Semarang who have worked at least one year . The results of this study indicate that Rumah Zakat Semarang has approached the implementation Islamic management in managing human resources. Islamic aspects indicated by inserting Islamic values in the practice of recruitment, selection and placement, training and development, performance appraisal and compensation.